INFLUENCE PRECEIVED CUSTOMER VALUE AND CUSTOMER SATISFACTION AGAINST CUSTOMER LOYALITY (CASE STUDIES IN THE TOURISM INDUSTRY THREE STAR HOTEL IN JEPARA) - Yuni Istanto (Jurnal Ekonomi Dan Bisnis, 2015)
Marketing in the twenty-first century experienced remarkable changes, with the inclusion of progress in the fieldof global information technology through the internet media. In this era many products / services that arepresented through the media, so that the consumer or customer before making a purchase will create aperceived value that customers (CPV) (Kotler, 2009: 134) about the product / service to be bought. The conceptof value is one of the basic elements of the theory of marketing (American Marketing Association, 2006 in AlbertGraf 2008). Identify and create customer value - understood as value for customers - regarded as an importantprerequisite for the success of the company in the future. Creating a loyal customer is the core of every business,one of the things that affect customer loyalty is to create value (Kotler, 2009: 134), the only value that can becreated company is the value derived from the customer, a value that is owned company now and the time willcome. A business is successful if it managed to obtain, maintain and grow the customer. In addition, factors thataffect customer loyalty (CL) is customer satisfaction (CS). This research applies the theory of Customer preceivedvalue via internet before choosing and buying services and hospitality and customer satisfaction after enjoyingthe hospitality of customer loyalty services at the three star hotel in Jepara. The purpose of this study was to testthe direct influence preceived Customer Value and Customer satisfaction to customer satisfaction on customers'three-star hotel in Jepara.  Keywords: Customer preceived value, customer satisfaction, customer loyalty.